Islamic Educations and Moral Development: Teachers Approaches in Shapping Students Character - Hasanah, Mizanul; Husna, Nurul (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Teachers can provide inspiration and guidance for children’s behavior. Therefore, teachers are always required to work hard to develop students’ potential so that students can understand their own potential. Included in the development of student morals, so that students can distinguish which one is good and which one works based on the reasons and norms that exist in the student environment. Moral development must start from the basic level so that students have a solid foundation in daily behavior. This research was conducted at MIS Nurul Huda Gebang Kab. Langkat uses qualitative research methods and descriptive qualitative methods as research objects. The results showed that MIS students Nurul Huda Gebang Kab. They have very diverse backgrounds; some people can read the Koran, but some still can’t read at all—the efforts of Ustad and Ustadzah (school teachers) MIS Nurul Huda Gebang Kab. Langkat strengthens the faith, piety, and morality of students in educating and fostering students; (1) carry out learning to read the Qur’an and read selected short surahs, (2) read daily prayers, (3) perform dhuha, dhuhur, and asar prayers in congregation, and (4) cultivate student morality. Supervised by MIS teacher Nurul Huda Gebang Kab. Langkat can be said to be successful; 100% of students have graduated by memorizing just 30 juz and the daily prayers after taking the final school exams.